1996
DOI: 10.1038/ng0996-82
|View full text |Cite
|
Sign up to set email alerts
|

A genome scan localizes five non–MHC loci controlling collagen–induced arthritis in rats

Abstract: Identification of specific genetic loci that contribute to susceptibility to rheumatoid arthritis (RA) in humans has been hampered by several factors, including: i) multiple interacting genetic loci contributing to susceptibility; ii) complex interactions of environmental and genetic factors; iii) genetic heterogeneity; and iv) low penetrance. We have, therefore, mapped quantitative trait loci (QTLs) that control inflammatory arthritis susceptibility and/or severity in progeny of two inbred rat strains with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
2
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 28 publications
10
138
2
1
Order By: Relevance
“…Amd1 and Asm1 may be a common locus for the same etiology of these 2 kinds of diseases. This is also the first study to map a gene locus for susceptibility to spontaneous arthropathy in DBA/1 mice, Amd2, on chromosome 3 in the region of a DBA/1 (14,22) and other mouse and rat models (23)(24)(25). However, the region of Amd2 did not share any of the loci involving the MHC.…”
Section: Discussionmentioning
confidence: 85%
“…Amd1 and Asm1 may be a common locus for the same etiology of these 2 kinds of diseases. This is also the first study to map a gene locus for susceptibility to spontaneous arthropathy in DBA/1 mice, Amd2, on chromosome 3 in the region of a DBA/1 (14,22) and other mouse and rat models (23)(24)(25). However, the region of Amd2 did not share any of the loci involving the MHC.…”
Section: Discussionmentioning
confidence: 85%
“…With regard to CIA in rats, most linkage analyses have been performed in the setting of bovine CIIinduced arthritis and in strain combinations other than E3 with DA (19)(20)(21)(22)(23). Therefore, in order to make a reasonable comparison of the genetic inheritance of CIA and PIA in rats, we performed linkage analysis of CIA in the same strain combination and induced by the same collagen source that was used for the PIA studies.…”
mentioning
confidence: 99%
“…Studies in rodent intercrosses identified several arthritis susceptibility, severity and chronicity loci (Table 1). 29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] The RA genome-wide family-based genetic studies were not designed or structured to address disease severity, histologic damage or the other arthritis-related phenotypes that can be studied in rodents. More recent cohorts have been incorporating severity and outcome parameters in their prospective data collection and will likely have a major role in RA severity genetic association studies.…”
Section: Inducible Modelsmentioning
confidence: 99%
“…For example, DA Â F344 F2 intercrosses studied for CIA identified six non-MHC loci, 40,43 while the same intercross studied for AIA led to the identification of only three non-MHC loci. Of these, only one non-MHC locus, Cia3/Aia3, was common to both models, while the others were model specific.…”
Section: Spontaneous Modelsmentioning
confidence: 99%
See 1 more Smart Citation